PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS DI SDN 14 SADIA KOTA BIMA - Nurhafidah; Wahyu Mulyadi; Abdussahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem-based learning teaching model has an important role in developing critical thinking skills, especially at the elementary school level. This research was conducted at SDN 14 Sadia Bima City to answer the obstacles or challenges faced by teachers in the implementation of the PBL learning model. The application of the PBL model not only trains students in critical thinking but students can also be active in group learning so that they can train students to respect each other's differences in opinion and the learning process in the classroom can be more active or not monotonous because PBL involves all students must be able to actively learn in class. The purpose of this study is to find out the extent to which the PBL model is applied to significantly improve critical thinking skills. Data was collected through observations, interviews with teachers and students, and documentation of teaching and learning activities in the classroom. The results of the study show significant results in the application of the PBL learning model in developing critical thinking skills where students are more active in learning, can solve a problem contained in a material together, can issue ideas in a sequence and students can dare to express opinions in accordance with the abilities possessed by students. This success is supported by the support of teachers and integrity in the use of the PBL model in several subjects. This research recommends that the PBL model continue to be developed as an effective strategy in teaching because it has a positive impact not only on the academic aspect but also on the development of character and skills in the 21st century.